2018
DOI: 10.1111/zph.12490
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic characterization of temporally related nontyphoidal Salmonella strains isolated from humans and food animals in central Ethiopia

Abstract: Salmonella is one of the common causes of food-borne bacterial illnesses. The primary sources of human nontyphoidal Salmonella (NTS) infection are food animals. This study characterized temporally and spatially related Salmonella isolated during April 2013 to March 2014 from faeces of diarrhoeic human patients in Addis Ababa (n = 68) and food animals (n = 84) in Addis Ababa and surrounding districts (dairy cattle, n = 30; slaughtered cattle, n = 20; poultry, n = 26; swine n = 8). Isolates were serotyped, page … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…Obesity has traditionally been regarded as an excessive energy state associated with diet and lifestyle. However, recent investigations indicate that obesity is a metabolic syndrome of complicated pathogenesis associated with genetic35 and environmental57 factors. Recently, the roles of estrogen, estrogen receptors (ERs) and the G protein-coupled estrogen receptor (GPER, previously termed GPR30) have garnered increasing attention.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity has traditionally been regarded as an excessive energy state associated with diet and lifestyle. However, recent investigations indicate that obesity is a metabolic syndrome of complicated pathogenesis associated with genetic35 and environmental57 factors. Recently, the roles of estrogen, estrogen receptors (ERs) and the G protein-coupled estrogen receptor (GPER, previously termed GPR30) have garnered increasing attention.…”
Section: Introductionmentioning
confidence: 99%
“…of Gram-negative isolates No. of ESBL (%) Abayneh M et al, 2018 [ 32 ] March to June 2016 Jimma 342 urine 74 17 (23.0) Abera B et al, 2016 [ 33 ] Sept 2013 to March 2015 Bahir Dar 477 blood, urine, pus/swab and body fluids 210 120 (57.1) Beyene G et al, 2011 [ 21 ] Jan to Aug. 2006 Addis Ababa 1225 stool, blood 113 78 (69.0) Desta K et al, 2016 [ 22 ] 10–20 Dec 2012 Addis Ababa 267 stool 295 151 (51.2) Eugale T et al, 2018 [ 23 ] April 2013 to March 2014 Addis Ababa 68 Stool 68 12 (17.6) Gashaw M et al, 2018 [ 24 ] May to Sept. 2016 Jimma 197 urine, swab/pus, blood, and sputum 100 36 (36.0) Legese et al, 2017 [ 25 ] Jan. to March 2014 Addis Ababa 322 blood and urine 28 22 (78.6) Mulisa et al, 2015 [ 26 ] April to Aug. 2016 Adama 384 urine, stool, swabs, and body fluids 65 17 (26.0) Mulualem Y et al, 2012 [ 27 ] Feb. to March 2007 Jimma 359 urine, stool, swabs, and sputum 67 24 (35.8) Pritsch M et al, 2017 [ 28 ] Jan. 2014 to June 2015 Jimma 224 ...…”
Section: Resultsmentioning
confidence: 99%
“…All of those were positive for ESBL-encoding genes: 82.7% (67/81) carried CTX-M-1 group and 17.3% (14/81) TEM. All CTX-M-1 group ESBL genes reported from included studies were confirmed to be CTX-M-15 genes [ 8 , 23 ]. Additional genes detected were: one isolate carrying a bla OXA gene from Addis Ababa, two bla CTX of the CTX-M-9 group [ 23 ] and three bla SHV genes only expressed in Enterobacter cloacae isolated in Jimma [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations